Isolated Segmental Humeral Shaft Fracture Without Vascular Compromise Complicated by Brachial Compartment Syndrome: A Case Report. Issue 4 (October 2019) - Sanders, Drew; Kelly, Drew; Starr, Adam
Abstract : Case: We report an unusual case of a closed humeral shaft fracture, with no vascular compromise, resulting in brachial compartment syndrome. Our patient was successfully treated with fasciotomy and external fixation, followed by staged open reduction and internal fixation and skin grafting. Conclusion: Although uncommon in the upper arm, suspicion for compartment syndrome should remain high for patients with unrelieved pain and swelling after humeral shaft fracture. Serial physical examination and invasive monitoring can assist in the diagnosis. Fasciotomy and staged fracture repair can yield good results.